The role of tradition in determining the winter distribution of Pinkfeet in Britain - Boyd, Hugh (Wildfowl, 1954)
559 recoveries and 155 recaptures of Pinkfeet ringed in Britain since 1950 provide some information on the distribution of the species in Britain. Ringed geese are probably fairly representative of unringed ones, but the conditions of their capture and recovery impose severe limits on the amount of detailed information they provide. Most marking of Pinkfeet in Britain has been done in October and November. There are evident tendencies for marked birds to remain in the areas where they were captured during the following winter, and to return to these areas in later years, particularly at the corresponding season. The proportions of geese remaining in, and returning to, an area show regional differences. The birds of the Tay, the Solway and Eastern England are relatively sedentary and strongly attached to those regions; those of South-East Scotland are relatively mobile. Pinkfeet marked as adults show greater attachment to the region of marking than those marked in their first autumn of life. These young birds behave like older ones caught in the same places during their first winter, as would be expected from the persistence throughout the winter of family groups in geese. But in their second and late winters they are more likely to visit other areas than are their parents. Adults marked in East England are relatively more sedentary than those marked in the Tay region of Scotland. The Pinkfeet frequenting the Humber and the Wash in autumn and winter appear to constitute a single population, rather distinct from the more northerly ones. Those wintering in Scotland are more difficult to segregate, although the Solway geese, those in Midlothian and those in Aberdeen remain more or less separate from the geese living in Fife, Kinross, Perth and Angus. Spring recoveries from North-East Scotland (where there is no effective close season inland) suggest that the English and the Scottish populations when on passage through North-East Scotland frequent the same areas, although the English and Solway birds appear only to visit Aberdeen while the geese which in autumn visit central Scotland move north into the Moray Basin as well as to Aberdeen, and go north earlier than the English birds. It is suggested that the historical evidence available is unsuitable for indicating the reasons for changes, or constancies, in the numbers of Pinkfeet frequenting various parts of Britain and that attempts should be made to collect better information.